Effect of Latin dance on physical and mental health: a systematic review - Xutao Liu; Kim Geok Soh; Roxana Dev Omar Dev (BMC, 2023)
Abstract Background Latin dance is a well-liked physical activity. It has gained increasing attention as an exercise intervention for improving physical and mental health outcomes. This systematic review examines the effects of Latin dance on physical and mental health. Methods Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) were used to report the data for this review. To gather research from the literature, we used recognized academic and scientific databases such SportsDiscus with Full Text, PsycINFO, Cochrane, Scopus, PubMed, and Web of Science. The systematic review only included 22 studies out of the 1,463 that matched all inclusion criteria. The PEDro scale was used to rate each study's quality. 22 research received scores between 3 and 7. Results Latin dance has been demonstrated to promote physical health by helping people lose weight, improve cardiovascular health, increase muscle strength and tone, and improve flexibility and balance. Furthermore, Latin dance can benefit mental health by reducing stress, improving mood, social connection, and cognitive function. Conclusions Finding from this systematic review provide substantial evidence that Latin dance has effect on physical and mental health. Latin dance has the potential to be a powerful and pleasurable public health intervention. Systematic Review Registration CRD42023387851, https://www.crd.york.ac.uk/prospero .